Digital note taking tool using a mediation approach / Mogeeb Ahmed Ahmed Mosleh - Mosleh, Mogeeb Ahmed Ahmed (2013)
Technology is used widely to serve education. However progress in transferring note taking into digital form age is slow. The necessity for digital note taking into digital era become importance because information resources were increased extensively where traditional note become insufficient to process these amounts of information. Digital notes are editable, searchable, portable, readable, can be indexed, linked, etc. Massive tools developed to bridge the gap between paper-based and technology-based notes. Unfortunately, these note taking tool still inadequate to replace the traditional approaches of note taking. This study investigates the limitations of typical note taking systems and discusses the implications on the design of future note taking applications. Developing successful note taking applications is a challenge because of the complexity, technology learning dilemma, integrity, and inefficiency issues. These challenges are stated in thesis statement to shape the solution for transmitting the traditional note taking into digital era. We proposed a framework to assist developer with specific guidelines about note taking roles, constraints, and responsibilities for a successful note taking application. The framework is meant here to resolve inefficiency, simplify complexity, and facilitate modular engineering to accelerate the development process of note taking systems. Additionally, intelligent mediator is proposed to resolve technology learning dilemma for smoothly moving into digital environments. A prototype called SmartInk was developed based on the framework principles. The prototype was integrated with specific mediation tools to demonstrate the functions of the mediator in transferring realistic tasks into digital environments. The system presented here was designed to provide similar functionality of traditional note taking on the Tablet PC. Data were collected using survey questionnaires, and server log data of user activities to explore usability of SmartInk. A total of 42 volunteers participated in the evaluation for a period of seven weeks. Six students used SmartInk every week to take their notes in classroom and review taken notes outside campus. Evaluation was conducted to test SmartInk’s effectiveness, usability, and efficiency for performing note taking tasks. An excellent result of evaluation system usability was obtained from the analysis of the data of student feedbacks, and server logs entries provided us with accurate summary about the student activities during interaction with the SmartInk system. Analysis of the server logs showed that all SmartInk functions were used frequently by students in an easy, efficient, and effective way. Based on evaluation results, we conclude that the combination of framework and mediator provide a solution to bridge the gap between traditional tasks of note taking and digital environments without losing learning consistency.